How Do CD4+ T Cells Detect and Eliminate Tumor Cells That Either Lack or Express MHC Class II Molecules? - Haabeth, Ole Audun Werner; Tveita, Anders Aune; Fauskanger, Marte; Schjesvold, Fredrik; Lorvik, Kristina Berg; Hofgaard, Peter O.; Omholt, Hilde; Munthe, Ludvig A.; Dembic, Zlatko; Corthay, Alexandre; Bogen, Bjarne (Frontiers in Immunology, 2014)
CD4+ T cells contribute to tumor eradication, even in the absence of CD8+ T cells. Cytotoxic CD4+ T cells can directly kill MHC class II positive tumor cells. More surprisingly, CD4+ T cells can indirectly eliminate tumor cells that lack MHC class II expression. Here, we review the mechanisms of direct and indirect CD4+ T cell-mediated elimination of tumor cells. An emphasis is put on T cell receptor (TCR) transgenic models, where anti-tumor responses of naïve CD4+ T cells of defined specificity can be tracked. Some generalizations can tentatively be made. For both MHCIIPOS and MHCIINEG tumors, presentation of tumor specific antigen by host antigen presenting cells (APCs) appears to be required for CD4+ T cell priming. This has been extensively studied in a myeloma model (MOPC315), where host APCs in tumor-draining lymph nodes are primed with secreted tumor antigen. Upon antigen recognition, naïve CD4+ T cells differentiate into Th1 cells and migrate to the tumor. At the tumor site, the mechanisms for elimination of MHCIIPOS and MHCIINEG tumor cells differ. In a TCR transgenic B16 melanoma model, MHCIIPOS melanoma cells are directly killed by cytotoxic CD4+ T cells in a perforin/granzyme B-dependent manner. By contrast, MHCIINEG myeloma cells are killed by IFN-g stimulated M1-like macrophages. In summary, while the priming phase of CD4+ T cells appears similar for MHCIIPOS and MHCIINEG tumors, the killing mechanisms are different. Unresolved issues and directions for future research are addressed.